Implementasi Model Discovery Learning Berbantuan Media Literasi Canva: Upaya Peningkatan Keterampilan Berbicara Siswa Kelas I SD Wonoplumbon 02 Semarang - Nafasha Audina; Panca Dewi Purwati (Mathematics Education Study Program, 2025)
This study was motivated by the speaking skills of lower grade students, which remain a challenge in Indonesian language learning, including in grade 1 at Wonoplumbon 02 Elementary School in Semarang. Although the students' reading skills are relatively good, many students still have difficulty expressing their opinions, pronouncing words clearly, and showing the courage to speak. The purpose of this study was to describe the application of the Discovery Learning model assisted by Canva literacy media and the effectiveness of the Discovery Learning model assisted by Canva literacy media in improving the speaking skills of first-grade elementary school students. The research method used was mixed methods with a concurrent embedded design, involving 23 students through observation and assessment of speaking performance. The results showed that Canva literacy media was able to increase learning enthusiasm and help students understand visual instructions more clearly. A total of 87% of students achieved KKTP, while 13% did not. Students showed improvement in articulation, courage, and the ability to answer simple questions, although there was a tendency to imitate their friends' reasoning when expressing their opinions. In conclusion, the integration of Discovery Learning and Canva is effective in improving students' speaking skills, but further strategies are needed to encourage diversity of reasoning and divergent thinking skills.